1988
DOI: 10.1037/0021-9010.73.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Compensation satisfaction: Its measurement and dimensionality.

Abstract: This research examined the influence of contextual variables on the factor structure of Heneman and Schwab's (1985) Pay Satisfaction Questionnaire (PSQ) and further explored the dimensionality of the compensation satisfaction construct. The PSQ is intended to measure four aspects of compensation: pay level, pay raises, pay structure-administration, and benefits. Previous research showed support for the pay level and benefit subscales, with equivocal results for the raises and structureadministration subscales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 16 publications
9
83
0
3
Order By: Relevance
“…L. Heneman et al, 1988;Judge, 1993;Judge & Welbourne, 1994;Lam, 1998;Mulvey, Miceli, & Near, 1992;Orpen & Bonnici, 1987;Scarpello et al, 1988). As summarized by H. G. Heneman and Judge (2000), these factor analytic studies have supported the notion of pay satisfaction as a multidimensional construct.…”
Section: The Psqmentioning
confidence: 70%
See 1 more Smart Citation
“…L. Heneman et al, 1988;Judge, 1993;Judge & Welbourne, 1994;Lam, 1998;Mulvey, Miceli, & Near, 1992;Orpen & Bonnici, 1987;Scarpello et al, 1988). As summarized by H. G. Heneman and Judge (2000), these factor analytic studies have supported the notion of pay satisfaction as a multidimensional construct.…”
Section: The Psqmentioning
confidence: 70%
“…One explanation for some of the inconsistent results obtained is that the factor structure, or number of factors, of the PSQ might depend on contextual characteristics. For instance, Scarpello et al (1988) found that the PSQ factor structure varied by job classification (exempt, nonexempt, and hourly) and by other organizational factors such as company labor-relations policy.…”
Section: The Psqmentioning
confidence: 99%
“…Finally, scientists have agreed that pay satisfaction is multidimensional (Heneman & Schwab, 1985;Scarpello, Huber, & Vandenberg, 1988). They proposed that pay satisfaction comprised four dimensions.…”
Section: Turnover Intention and Pay Satisfactionmentioning
confidence: 99%
“…Third, there is considerable evidence that compensation satisfaction is a multidimensional construct although there is no universal agreement whether there are three (Carraher, 1991;Scarpello, Huber and Vandenberg, 1988), four (Heneman, Greenberg and Strasser, 1988;Heneman and Schwab, 1985;Judge, 1993;Scarpello, Huber and Vandenberg, 1988), or five (Garcia and Posthuma, 2009;Mulvey, Miceli and Near, 1992) dimensions. Yet, as Lum et al (1998) note, many pay satisfactionturnover studies have used unidimensional constructs to measure pay satisfaction (see for example, Keaveny and Inderrieden, 2000), or focused on only one aspect of pay satisfaction, usually pay level (see Williams, McDaniel and Nguyen, 2006, for a meta-analysis of pay level satisfaction).…”
Section: Introductionmentioning
confidence: 99%